Experimental Evaluation of Thermo-Mechanical Properties of GRCop-42, Produced by PBF-LB, at Low Temperatures - Daniele Cortis; Cristina Giancarli; Francesco Ferella; Chiara Di Donato; Riccardo Elleboro; Alessandro Razeto; Stefano Nisi; Donato Orlandi (Metals)
Today, Powder Bed Fusion-Laser Based technology is widely used in many industrial fields, but some high-demanding applications are still not fully investigated, such as low temperatures. In basic physics research, experiments usually use low temperatures to reduce external influences and to increase the sensitivity of particle detectors, accelerators, etc. The production capabilities of this technology have become a standard for manufacturing such components, and the demand for high performance has led to the investigation of new materials, like GRCop-42. It possesses excellent thermal properties and strength at high temperatures, and although several works have been published in recent years, full research on its behaviour at low temperatures is still missing. The aim of the paper is to investigate the mechanical properties of GRCop-42, produced by PBF-LB, from low to room temperature, like Elastic Modulus and Poisson’s ratio, and correlate them with thermal conductivity in the as-built state and after heat treatment. The results showed that the material can maintain high strength even at low temperatures, without losing ductility and the ability to store strain energy; moreover, after heat treatment, it increases its thermal properties due to the way the precipitates are dispersed in the copper matrix.